Single dose (400mg) versus 7 day (200mg) daily dose itraconazole in the treatment of tinea versicolor: a randomized clinical trial (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):72-76.The abstract of this article is available on the PubMed website